Find you First - Barclay, Linwood (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2021)
Tech millionaire Miles Cookson has more money than he can ever spend, and everything he could dream of--except time. He has recently been diagnosed with a terminal illness, and there is a fifty percent chance that it can be passed on to the next generation. For Miles, this means taking a long hard look at his past... Two decades ago, a young, struggling Miles was a sperm donor. Somewhere out there, he has kids--nine of them. And they might be about to inherit both the good and the bad from him--maybe his fortune, or maybe something much worse. As Miles begins to search for the children hes never known, aspiring film documentarian Chloe Swanson embarks on a quest to find her biological father, armed with the knowledge that twenty- two years ago, her mother used a New York sperm bank to become pregnant. When Miles and Chloe eventually connect, their excitement at finding each other is overshadowed by a series of mysterious and terrifying events. One by one, Miless other potential heirs are vanishing--every trace of them wiped, like they never existed at all. Who is the vicious killer--another heir methodically erasing rivals? Or is something even more sinister going on? Its a deadly race against time...
Keywords: Rich people -- Fiction; Terminally ill -- Fiction; Inheritance and succession -- Fiction; Murder -- Fiction; Thrillers (Fiction)